Hubungan Regulasi Emosi dengan Prokrastinasi Akademik Pada Siswa - Muti’ah, Aulia; Wisma, Nur; Mega Putri, Rani (Islamic Counseling: Jurnal Bimbingan Konseling Islam, 2024)
The Covid-19 era has brought new habits for students, one of which is taking work as a relaxing activity. This arises because of the comfort zone that was formed to entertain oneself in that era. However, this has negative effects on students' academic aspects, for example academic procrastination. Academic procrastination is influenced by many factors, one of which is emotional regulation. A preliminary study conducted with student interviews at SMAN 10 Palembang showed that students can regulate emotions but they still carry out academic procrastination. This research was carried out using a quantitative correlational model method because it wanted to examine whether or not there was a relationship between emotional regulation and students' academic procrastination and was carried out by distributing questionnaires to 85 students as a sample. The results obtained in this research are the most data at the level of emotional regulation 72% and academic procrastination 69%, which is in the "medium" category and produces -0.057 as a Spearman rank correlation value which shows that there is a very weak and unidirectional relationship between emotional regulation and Academic procrastination in class.